Air Transport : Annual Report 2021 - World Bank (Washington, DC, 2022)
Air transport plays an important role in fostering development, particularly in facilitating economic integration, generating trade, promoting tourism, and creating employment opportunities. It facilitates integration into the global economy and provides vital connectivity on a national, regional, and international scale. However, in many countries, air transport equipment and infrastructure, regulat ory frameworks, and safety and security oversight systems are inefficient or inadequate. In view of these challenges and to assist clients in establishing a safe, secure, cost-efficient, accessible and reliable air transport network, the Bank is mandated to undertake the following major activities: (i) Operational work through projects and technical assistance; (ii) Economic sector work, research, and knowledge dissemination on air transport related issues; (iii) External relations and collaboration with partner organizations and (iv) External relations and collaboration with partner organizations. This report focuses on Air transport portfolio and project highlights for the year 2021.